Sistem Informasi Penggajian Berbasis Web pada AP Express Cimanggu - Yusuf, Dede; Moch. Hasymi Somaida (Jurnal Teknologi dan Bisnis, 2022)
AP Express is a business engaged in groceries and office equipment. As a fairly large business, AP Express still uses a manual system in its employee payroll process. The solution for solving payroll problems at AP Express is by building a web-based payroll information system to minimize errors and archive the required data. Literature study is a research method used to collect data, namely managing data from information by reading books and searching the internet, as well as conducting interconnected observations and interviews to collect data directly from informants. The purpose of this research is to find out, the purpose of this research is to find out, describe and analyze the use of the payroll system in AP Express. This research produces a web-based payroll information system, and this can overcome the problems and constraints that existed in the old system so that it is able to meet all system requirements. The conclusion of the research results is that this web-based payroll information system is applied directly to the solution section to improve the performance of the integrated system so that accurate, fast and efficient payroll report results are obtained.